Optimization on flow field in an operational cleanroom subject to kinematic component and structural parameters - Liu, Kun; Hao, Ming; Li, Bangyu; Guan, Tianen; Chen, Shulei; Wang, Guipeng; Xie, Yuanhua; Bian, Xin (Journal of Building Engineering, 2022)
Due to the high uniformity and stability of streamline, unidirectional cleanrooms are widely used in semiconductor clean workshops. However, the moving parts and complex process of production in the cleanrooms may cause disturbance of the streamline, leading to increased contamination. In this study, a small wafer transport cleanroom with a SCARA (selective compliance assembly robot arm) as a moving part is considered, and a numerical method of overset mesh together with the momentum source method is employed to simulate the flow field, which is compensated with experimental measurements. Hence, taking the nonuniformity and air age as the indicators to evaluate the airflow and particulate emission efficiency of the cleanroom, nine influencing factors are investigated by making orthogonal simulations. This includes the velocity, the height, the cross-section area, and the moving range of the SCARA, the velocity of supplied air, the blowing ratio, and the distribution of the Fan Filter Units, the height and the grid porosity of the cleanroom. The optimal results alleviate the average and standard deviation of nonuniformity by 6.22% and 33.39%, respectively, compared with the original design of a factory. The particulate emission efficiency of the flow field is also significantly improved. Furthermore, the results inspire a potential optimal design for cleanrooms with dynamic loads in typical semiconductor processes. •Overset simulation method with low error for dynamic airflow is proposed.•Momentum source method is utilized to simulate the air age of the cleanroom.•Nine-factor orthogonal simulations are designed to explore the parameter space.•Optimization recommendations for operational cleanrooms are proposed.